PRELIMINARY RESEARCH PENGEMBANGAN MODUL BERBASIS PROBLEM BASED INSTRUCTION PADA MATA KULIAH FISIKA MATEMATIKA I DI STKIP PGRI SUMATERA BARAT - Iing Rika Yanti; Silvi Trisna; Usmeldi Usmeldi; Ramli Ramli (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Mathematical Physics I is one of subjects for Physics Education’s department on STKIP PGRI West Sumatra. Mathematical Physics give you the basics of mastering the mathematical methods used in discussing the physical phenomena of nature. This course requires students to work hard in mastering the concept given. Therefore we need a teaching material in the form of modules that are effective in improving student understanding of concepts. Modules that developed serves to improve the mindset of students to think critically, creatively, and innovative (Problem Based Instruction). Students are given the opportunity to develop their creative ideas in solving the problems that can develop critical thinking skills, so that students are able to associate the concept of mathematics with physics concepts. In this research, preliminary analysis in the form of a needs analysis and analysis of concepts or content, and assessment of the necessary literature in the lecture. Analysis of the concept aims to define the content and course materials are needed in developing the module. In the study of literature in the form of an assessment of the existing teaching materials to be developed for the better. Based on the initial investigation (preliminary research) performed on students and colleagues agree to the development of module-based Mathematical Physics 1 Problem Based Instruction as teaching material in the lecture. Keywords:Preliminary Research, PBI, Mathematical Physics I